Penerapan Model GEMAR untuk Meningkatkan Keterampilan Berpikir Kritis, Kerja Sama, dan Komunikasi Siswa Kelas V pada Pembelajaran IPAS - Ila Agustin; Yogi Prihandoko (Mataram University, 2026)
This study was motivated by the low levels of critical thinking, collaboration, and communication skills of fifth-grade students in IPAS learning at SDN Kuin Selatan 5 Banjarmasin. The learning process was still teacher-centered, resulting in limited student participation and suboptimal learning outcomes. This study aimed to describe teacher and student activities and to analyze the improvement of students' critical thinking, collaboration, and communication skills through the implementation of the GEMAR learning model, which combines Problem Based Learning (PBL), Numbered Heads Together (NHT), and Team Games Tournament (TGT). This research employed Classroom Action Research conducted in four meetings involving 12 fifth-grade students. Data were collected through observation sheets of teacher activities, student activities, critical thinking skills, collaboration skills, communication skills, and learning achievement tests. The data were analyzed descriptively using percentages and improvement trends across each meeting. The findings revealed that teacher activities improved from the good category to the very good category, while student activities reached the very active category. Students' critical thinking, collaboration, and communication skills also improved consistently and achieved the predetermined success indicators. These improvements contributed to better learning outcomes both individually and classically. Therefore, the GEMAR learning model effectively enhances the quality of IPAS learning by improving teacher activities, student participation, critical thinking, collaboration, communication, and learning outcomes.